Non-directed postmortem sperm donation: some questions. Issue 4 (4th August 2020) - Kroon, Frederick; Kroon, Ben
Abstract : In their recent 'The ethical case for non-directed postmortem sperm donation', Hodson and Parker outline and defend the concept of voluntary non-directed postmortem sperm donation, the idea that men should be able to register their desire to donate their sperm after death for use by strangers since this would offer a potential means of increasing the quantity and heterogeneity of donor sperm. In this response, we raise some concerns about their proposal, focusing in particular on the fact that current methodologies do not make for a reliable way of ensuring that sperm retrieved postmortem has a good chance of leading to conception, which is in turn likely to make potential recipients reluctant to use such sperm. These concerns add to the ethical doubts that attend aspects of the proposal, making the prospect of implementation of such a policy unlikely at best.